Maize production in Mali: microdosing and mechanization for better yields, profits, and labor reduction - Woumou Kamkam; Adama Coulibaly; Jens B. Aune (Discover Agriculture)
Abstract This study aimed to determine the optimal maize NPK microdosing rate in Mali and compare labor requirements for mechanized versus manual sowing and fertilization across three locations with varying rainfall. The treatments included six microdosing rates, ranging from zero to 93 kg NPK/ha (3 g NPK/hill), and the recommended rate of 100 kg NPK/ha applied by row application. All treatments received an additional 150 kg urea/ha. Grain yield was significantly increased with NPK application up to 93.7 kg/ha, resulting in a 61.3% (1029 kg/ha) yield increase compared to the control. The 63 kg NPK/ha microdosing rate provided a yield and economic return comparable to 100 kg NPK/ha using row placement. Profitability was assessed under both unfavorable and favorable fertilizer-to-grain price ratios. The 78.1 kg NPK/ha rate yielded the highest gross margin and value-cost ratio (VCR) across both price scenarios. The VCR exceeded the critical threshold of two in all fertilizer treatments, even under high fertilizer costs, indicating low financial risk even without subsidies. The labor analysis showed that mechanized sowing and fertilization saved 10 man-days/ha compared to manual methods, ensuring timely planting. Given the labor intensity, farmers are unlikely to adopt manual microdosing without mechanization. In conclusion, combining fertilizer microdosing with mechanization improves fertilizer use efficiency, reduces labor-use, and ensures timelier sowing, thereby contributing to enhanced climate resilience.